زوائد كتاب "التشرُّف بمعرفة أحاديث التصوُّف" للشيخ التهانوي على الكتب الستة : دراسة تحليلية نقدية - وصي الله
This research aims to study the Hadiths mentioned in the book of al-Tashrruf bi M'arifah Ahadith al-Tasawuf, by Sh. Ashraf Ali Thanwi which are not mentioned in the six collections of Hadith via analytical and critical perspective. The researcher aims to know the level of authenticity of such Hadith because the Hadiths mentioned in the six collections of Hadith are usually attributed either to Sahih or Hasan category. However, Hadiths not mentioned in these collections need to be studied in line with the methodology of Hadith experts by referring them to their original references and determining the degree of the Hadith in terms of acceptability or rejection. Sh. Thanwi collected a number of Hadiths to support practices of Tasawuf and to criticize those who were critical of Tasawuf's opinions or those who rejected outright Tasawuf. Despite this, Sh. Thawni did not refer to the original sources of these Hadith and did not evaluate it as per the methodology of Hadith science. To address this gap, the researcher checked the authenticity of eighty-nine Hadiths from al-Tashrruf bi M'arifah Ahadith al-Tasawuf wherein he highlighted the original sources of the Hadith and explained the opinions of Hadith scholars on such Hadiths. Also, the researcher expanded in his authenticity search in other books of Hadith and opined about each Hadith based on the description of each narrator in each or most of the lines of narration. The researcher used two methods: a) critical method by highlighting the level of Hadith in terms of acceptability or rejection, and b) analytical method by analyzing the opinions of critics of Hadith narrators in relation to narrators and level of Hadith.